Enhanced photocatalytic hydrogen production from aqueous-phase methanol reforming over cyano-carboxylic bifunctionally-modified carbon nitride. Issue 83 (2nd October 2019) - Tan, Hao; Kong, Peng; Liu, Meixian; Gu, Xianmo; Zheng, Zhanfeng
Abstract : Polymeric carbon nitride is a promising candidate for metal-free photocatalysis, but it is hampered by low activity due to poor carrier separation efficiency and lack of active sites. Abstract : Polymeric carbon nitride is a promising candidate for metal-free photocatalysis, but it is hampered by low activity due to poor carrier separation efficiency and lack of active sites. We have constructed a bifunctionally-modified structure, containing cyano groups internally and carboxyl groups on the surface, that was about 205 times more active than unmodified carbon nitride. The internal cyano groups enhanced the photoelectric performance of carbon nitride, while the surface carboxyl groups acted as active sites to promote hydrogen production. It is anticipated that this work will inform the rational design of polymeric carbon nitride and inspire similar attempts to modify polymers.